A case of cranial autonomic dysfunctions predominant migraine: Migraine sans ache - Singh, Amit Shankar; Singhvi, Jeenendra Prakash; Mann, Harpreet Singh (Indian Journal of Case Reports, 2021)
Pain is the essential part of migraine headaches along with other features, whereas, cranial autonomic symptoms (CAS)/signs are a predominant and essential part of trigeminal autonomic cephalalgias. What if other features of migraine are present but the pain is absent? One such variation in migraine symptomatology is reported in this case, where the pain was not there but CAS/signs were predominant along with other features of migraine. The possible mechanism for such variation, in this case, maybe desensitization of afferent loop (comprised by nociceptors in extracranial and intracranial pain-sensitive structures supplied by the trigeminal nerve) and direct activation of the trigemino-cervical complex and brainstem structures causing dissociation of pain from the rest of the features of migraine. In this case, as the pain part gets completely dissociated from CAS/signs, hence this condition can be termed as “migraine sans ache.” The patient was started on anti-migraine treatment and she responded wonderfully